Self-determined forms of motivation predict sport injury prevention and rehabilitation intentions - Chan, Derwin King Chung; Hagger, Martin (Sports Medicine Australia, 2012)
Objectives: Two studies were conducted to examine how motivational regulations from self-determination theory (SDT) influenced athletes’ intentions towards sport-injury rehabilitation (Study 1) and prevention behaviours (Study 2) using the theory of planned behaviour (TPB) as a framework. Design: A cross-sectional survey was employed. Methods: Elite athletes (Study 1: N = 214; Study 2: N = 533) completed the Treatment Self-Regulation Questionnaire and psychometric measures of constructs from the TPB, with respect to their rehabilitation from sport injury in a hypothetical scenario (Study 1), or their injury prevention experiences (Study 2). Results: Partial least squares path analytic models indicated acceptable fit of the hypothesised model in all samples, and consistently found in both studies that autonomous motivation from SDT was positively associated with attitudes, subjective norms and perceived behavioural control from the TPB, and these three TPB variables positively predicted intentions of injury rehabilitation and prevention. Controlled motivation from SDT was, unexpectedly, positively linked to intentions, but the effect was smaller than that for autonomous motivation. Conclusions: Motivational regulations from SDT might serve as sources of information that influence athletes’ intentions through their impact on the attitude, perceived social norm and controllability of injury rehabilitation and prevention.